HUBUNGAN BEBERAPA FAKTOR WANITA PUS DENGAN PERNIKAHAN USIA DINI DI KECAMATAN CILACAP UTARA TAHUN 2016 - Yuanita Erry Wijati; Atik Mawarni; Djoko Nugroho; Sri Winarni (Jurnal Kesehatan Masyarakat (Undip), 2018)
Marriage at an early age is a marriage conducted by a woman at the age less than 20 years. Based on data from KUA in North Cilacap District in 2016, child bearing age woman who married at an early age as much as 9.3%, with the percentage in each sub-district is 22.5% in Gumilir, 25.4% in Mertasinga, 35.2% in Tritih Kulon, 12.7% in Karang Talun, and 4.5% in Kebon Manis. Cilacap regency ranked 7th for Mother's death. The purpose of this study is to analyze several factors related to women of child bearing age with early marriage in North Cilacap District.This type of research is an explanatory research with design cross sectional study. The study population are 765 child bearing age women and the number of samples 119 child bearing age women who were married in January-December 2016 and was recorded at KUA of North Cilacap District. The samples are taken by probability sampling. Data analysis is using univariate analysis, bivariate analysis with chi-square (α=5%) and multivariate analysis using logistic regression. The result of univariate analysis showed 56.3% of child bearing age women in advanced education group, 64.7% parent education in elementary education group, 56.3% parent with low economic status, 56.3% child bearing age women with bad promiscuity, 68.1% cultures that support an early marriage, and 47.1% child bearing age women married at an early age. The result of chi-square analysis is that there were relations of child bearing age women in advanced education (p-value= 0,001), parent education (p-value= 0,001), parent economic status (p-value= 0,001), promiscuity of child bearing age women (p-value= 0,018) and culture (p-value= 0,007) with an early age marriage. The result of multivariate analysis showed that there were influences of child bearing age women in advanced education (exp B=13,800), promiscuity of child bearing age women (exp B=4,491), parent education (exp B=4,129), with an early age marriage. Suggestion to minimize early marriage flight that is government of Cilacap Regency need to promote 12 year compulsory education, the need of supervision of parents to his daughter in associate and choose friend of opposite sex